Obesity in Arabic-Speaking Countries - Mohammad Badran; Ismail Laher (Journal of Obesity)
Obesity has reached epidemic proportions throughout the globe, and this has also impacted people of the Arabic-speaking countries, especially those in higher-income, oil-producing countries. The prevalence of obesity in children and adolescents ranges from 5% to 14% in males and from 3% to 18% in females. There is a significant increase in the incidence of obesity with a prevalence of 2%–55% in adult females and 1%–30% in adult males. Changes in food consumption, socioeconomic and demographic factors, physical activity, and multiple pregnancies may be important factors that contribute to the increased prevalence of obesity engulfing the Arabic-speaking countries.